Sifat fisik dan organoleptik tepung rumput laut Gracilaria verrucosa dari berbagai penanganan: Physical and organoleptic characteristic of Gracilaria verrucosa seaweed flour from various handlings - Hudi, Lukman; Alfiyanti, Trisca Yuniar; Utami, Rahma (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2023)
Gracilaria verrucosa one of the seaweed that is abundant but yet to be fully developed in optimum manner. This seaweed contains polysaccharides, protein, lipids, vitamins, polyphenols which can be used as nutraceutical food, besides soluble and insoluble fiber which can reduce diabetic, heart disease and cancer. This research aimed to identify various handling treatments of the physical properties and organoleptic of Gracilaria verrucosa flour. Methods used the Randomized design with 6 treatments, which are fresh seaweed, dried seaweed, dried seaweed with treatment 4% KOH and 24 hours fermented wish S.cerevisiae. The handling treatment had a significant effect except on the physical properties of color and organoleptic aroma. The best treatment was the treatment of Gracilaria verrucosa drying 10 hours + 4% KOH extraction + drying cabinet dryer) which resulted in an average moisture content of 12.48%, yield 19.175%, density 0.624%, viscosity 75.4 cps, color (L*a* b) 25.08*-4.36% 1.38, color organoleptic 5.13 (rather like) and aroma organoleptic 4.80 (ordinary-rather like).